AGROMETEOROLOGICAL GROUNDING OF THE TERMS OF SOWING OF WINTER RAPE IN THE STEPPE ZONE OF UKRAINE - Курцев, В. О. (Scientific Progress & Innovations, 2014)
The researches have established that a significant loss of plants of winter rape in winter caused a number of factors: the excessive development of the shoots in the autumn, the lack of well-developed root system and so on. In this regard, much attention should be paid to the terms of sowing of a crop. From this point of view, the best period of sowing is considered to be that, which will ensure the optimal growth of plants during the autumn vegetation. A choice of a term of sowing should be individualized for both a zone of growing and for growing conditions of each specific farm. A basis of the acceptance of a decision should be a long-term monitoring of a temperature, a frequency, an amount and a nature of precipitations, both in a pre-sowing period and during the emergence of the shoots and development of the plants, dates of a stopping of a vegetation of plants. The most optimal term for sowing of winter rape in the Steppe zone of Ukraine is the time from August 25 to September 5, the optimal permissible from August 20 to September 10. The date of maximum permissible threshold of optimal term of sowing of winter rape is September 5-10. The limitative factor in this range is the presence of moisture in the soil and loss of effective rainfall in this period.